"Tämä jos mikä, pitäisi kyllä forwardata jonnekin" : Finnish to English Code-switching in Social Media Posts - Töykkälä, Alexa (My University, 2026)
The aim of this study is to examine the various communicative functions of Finnish to English code-switching in social media posts, as well as to inspect which function is the most common out of the range of options. The data was collected from the app X from 33 users, using a specific set of keywords. The result of this study is that the users employed a range of functions, including quotation, interjection, reiteration, message qualification, self-presentation, humour and convenience. Furthermore, the study demonstrated that convenience, self-presentation and humour emerged as the most frequent functions. This research could be beneficial for multilingual interaction research.
Keywords: code-switching; intra-sentential code-switching; finglish; suomi-englanti; communicative functions; social media